TOXICITY TEST OF EXTRACTS OF THE FOUR SEA CUCUMBER (FAMILY HOLOTHURIIDAE) FROM EAST PENJALIRAN ISLAND, SERIBU ISLANDS, JAKARTA BASED ON THE BRINE SHRIMP LETHALITY TEST (BSLT) - Arum Albuntana; Yasman Yasman; Wisnu Wardhana (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2011)
Sea cucumber is one of the marine bioactive compounds resources . The properties of the bioactive compound are biologically shown by their functions as anticancer, antifungi, hemolytic, and immunomodulatoryt. The purpose of this research is to predict (determine) the toxicity level of the extracts of Actinopyga miliaris, Holothuria leucospilota, Bohadschia argus, and Bohadschia marmorata collected from Penjaliran Timur Island, Seribu Island National Park Jakarta. The method used in this research is Brine Shrimp Lethality Test (BSLT). The result of this research showed that all of the extract from those species are active in BSLT, indicated by LC50 values of less than 1000 μg/ml. Bohadcshia argus is highest active species indicated by LC50 value 69,254 μg/ml. Water fraction of H. leucospilota’s crude extract is the most active fraction indicated by LC50 50,968 μg/ml.Keywords: Brine Shrimp Lethality Test, Crude Extract, Fractionation, Family Holothuriidae, Sea Cucumber